The art of secrets - Klise, James, 1967- (Algonquin, 2014)
When some quirky art donated to a school fundraising effort to help a Pakistani American family, victims of a possible hate crime, is revealed to be an unknown work by a famous outsider artist, worth hundreds of thousands of dollars, adults and teenagers alike debate who should get the money and begin to question each other's motivations.